Strengthening Destination Image through the Arakan Sahur Festival to Increase Tourist Visits in West Tanjung Jabung Regency - Tiara Sabrina; Wahyu Rohayati; Hapsa (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the strengthening of destination image through the Arakan Sahur Festival in increasing tourist visits in West Tanjung Jabung Regency. The background of this study is based on the suboptimal use of festivals as a strategic instrument in building destination image, despite having strong cultural potential and high tourist attractions. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, documentation, and questionnaires as supporting data, involving the Tourism Office, the organizing committee, MSMEs, cultural communities, and tourists. Data analysis uses the Place Branding theory by Simon Anholt which includes six dimensions, namely presence, place, potential, pulse, people, and prerequisites. The results show that the Arakan Sahur Festival contributes to strengthening the destination image, particularly in terms of popularity and socio-cultural dynamics. However, image strengthening is not optimal due to limitations in facilities, environmental management, and consistency of public communication. Nevertheless, this festival is able to increase tourist visits and community economic activity. This study concludes that strengthening destination image through cultural festivals requires an integrated, collaborative, and sustainable strategy to improve regional tourism competitiveness.